2017
DOI: 10.4194/1303-2712-v17_4_18
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Agricultural pesticides, eventually find their ways to aquatic ecosystems by different routes adversely affect the aquatic biota. To determine its potential hazards, acute toxicity tests (LC50) of three commonly used organophosphate pesticides, Envoy 50SC, Samcup 50EC and Dursban 20EC on Labeo rohita and Barbonymus gonionotus were performed. The LC50 (P<0.05) of these pesticides were estimated at 0.110 (0.060-0.199), 0.217 (0.204-0.231) and 0.079 (0.073-0.084) ppm for L. rohita and 0.471 (0.440-0.500), 0.789 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Yang, Zha, Li, Li and Wang (2010) found lesions in kidney tissues including an extensive expansion in the lumen, degenerative and necrotic changes of tubular epithelia, and shrinkage of the glomeruli at 10 μg −L of atrazine exposed to rare minnow (Gobiocypris rarus) for 28 days. Reza et al (2017) found mild vacuole, degenerating kidney tubule and hemorrhage at 0.058 ppm in Labeo rohita and at the same dose, the kidney tissues of B. gonionotus appeared normal but some melanin pigment and vacuoles were also observed in these tissue samples. Pathology included moderate hemorrhage, pyknosis, hyaline for L. rohita were found in the kidney of fishes treated at 0.108 ppm Envoy 50 SC, and moderate vacuole, pyknosis and necrosis for B. gonionotus were found.…”
Section: Histopathological Observation In Pesticide Treated Fishmentioning
confidence: 77%
See 3 more Smart Citations
“…Yang, Zha, Li, Li and Wang (2010) found lesions in kidney tissues including an extensive expansion in the lumen, degenerative and necrotic changes of tubular epithelia, and shrinkage of the glomeruli at 10 μg −L of atrazine exposed to rare minnow (Gobiocypris rarus) for 28 days. Reza et al (2017) found mild vacuole, degenerating kidney tubule and hemorrhage at 0.058 ppm in Labeo rohita and at the same dose, the kidney tissues of B. gonionotus appeared normal but some melanin pigment and vacuoles were also observed in these tissue samples. Pathology included moderate hemorrhage, pyknosis, hyaline for L. rohita were found in the kidney of fishes treated at 0.108 ppm Envoy 50 SC, and moderate vacuole, pyknosis and necrosis for B. gonionotus were found.…”
Section: Histopathological Observation In Pesticide Treated Fishmentioning
confidence: 77%
“…Necrotic foci and lipid droplets in liver of Cyprinus carpio and interactions of antioxidant enzyme activity and lipid peroxidation effect on pesticides were recorded by Oropesa, Cambero, Gómez, Roncero and Soler (2009); Karaca et al, (2014) and Cagdas et al, (2017). Reza et al (2017) additionally found mild changes in vacuole, hemorrhage, and fatty degeneration in the liver tissues of L. rohita treated with 0.058 ppm Envoy 50 SC, whereas moderate hemorrhage, fatty degeneration, lipid droplets were observed for the same fish species at 0.108 ppm.…”
Section: Histopathological Observation In Pesticide Treated Fishmentioning
confidence: 85%
See 2 more Smart Citations
“…Toxic organic pollutants that include a large number of agrochemicals, such as pesticides, many of which are non-biodegradable and carcinogenic, are consistently being used in crop fields. As a result, fish and other aquatic biota, exposed to the pesticide-contaminated water are at much higher risk of dying (Katagi, 2010;Reza, Rakhi, Hossen, & Hossain, 2017). Seepage of pesticides into rivers and streams can be highly lethal to aquatic life and often might change the bionetwork of a particular area (Mensah, Palmer, & Muller, 2014;Sánchez-Bayo, Goka, & Hayasaka, 2016).…”
Section: Introductionmentioning
confidence: 99%